Tinjauan Fikih Muamalah terhadap Jual Beli Limbah Hewan Ternak untuk Budidaya Maggot Black Soldier Fly - Nendiarti Juniar; Zia Firdaus Nuzula (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. The practice of Sale and Purchase which has an indication of being unclear whether trading is permissible or not is the sale and purchase of livestock waste, because the traded waste consists of blood, carcasses and rotting animal body parts which are categorized as unclean objects. Based on the background and discussion of the problem, the research was focused with the aim of knowing the review of muamalah fiqh on the sale and purchase of livestock waste for the cultivation of maggot black soldier fly on the Maggot BSF